2011
DOI: 10.1007/s11769-011-0482-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reclamation time and land use on soil properties in Changjiang River Estuary, China

Abstract: The objective of this study is to analyze soil physical and chemical properties, soil comprehensive functions and impact factors after different years of reclamation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 20 publications
6
24
0
Order By: Relevance
“…For nitrate nitrogen and available P, the contents showed an initial increase, followed by a decrease over time, with 55 years being the turning point. Similar results were also reported in coastal reclaimed soils of Eastern China [8]. Overall, fertilizer application may also cause the soil nutrient contents to increase obviously, especially in the first 25 years of reclamation, while the tendency is to remain unchanged or even decrease after the 85 years in our study.…”
Section: Variance Analysis For Soil Properties In Different Zonessupporting
confidence: 90%
See 1 more Smart Citation
“…For nitrate nitrogen and available P, the contents showed an initial increase, followed by a decrease over time, with 55 years being the turning point. Similar results were also reported in coastal reclaimed soils of Eastern China [8]. Overall, fertilizer application may also cause the soil nutrient contents to increase obviously, especially in the first 25 years of reclamation, while the tendency is to remain unchanged or even decrease after the 85 years in our study.…”
Section: Variance Analysis For Soil Properties In Different Zonessupporting
confidence: 90%
“…Numerous studies of reclamation-induced changes in soil function have therefore been conducted. Portnoy and Giblin [7] and Sun et al [8] found that soil bulk density tended to increase, while soil moisture, electrical conductivity, and particle size tended to decrease during reclamation. Li et al [9] have suggested that soil nutrient distribution was significantly affected by land-use intensity after land had been reclaimed, with relatively high soil salinity in aquaculture ponds and high soil organic matter (SOM), available phosphorous (AP), and nitrate nitrogen (NO 3 − -N) contents in agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…Land use change is always accompanied by changes in soil physical–chemical properties (Sun et al, 2011). It is widely argued that the SOC increases as soil BD decreases, because of the increase in soil porosity and soil aggregate stability (Whalen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ninety percent of the entire coastline along the Jiangsu coast is tidal flat [54]. Research shows that the coastal tidal flat is currently expanding seaward at a rate of ±20 cm per year [55][56][57]. The study area, which is about 0.38 million ha, including part of the Yellow Sea and South Yellow Sea Radial Sand Ridges, is located in the central part of the coastal zone of Jiangsu Province (Figure 2).…”
Section: Study Areamentioning
confidence: 99%